?PROCESSING OF EMERALD BEARING ROCKS OF GUJAR KILLI EMERALD MINE BY WASHING AND SCREENING (Biological Sciences - PJSIR, 1994)
The recovery process of talc and emeralds, contained in the .emerald bearing altered talcose schists of Gujar Killi were found to be feasible at the bench and pilot plant scale. The various units required for the washing and screening plant were tested. A detailed investigation of size analyses of the head and ground samples, liberation and association of emerald/gangue particles, pulp density, product size analysis and optimisation of grinding were undertaken. A tentative block diagram was developed as aresult oflaboratory tests. The study conducted for the Gem Stone Corporation of Pakistan is encouraging and can be applied to the mechanical recovery of talc and emerald in the Gujar Killi emerald mme.